Calvin dan Potensi Pemikirannya bagi Ibadah Kristen - Kristanto, Billy (Veritas : Jurnal Teologi dan Pelayanan, 2020)
Calvin and the Potential of His Thought for Christian Worship. This article presents the potential of some of John Calvin's thoughts on Christian worship for today and the future. Worship according to Calvin does not seem promising to be developed in the present context because it is often considered too narrow. This article seeks to present a contrary perspective without intending to show the superiority of Calvin’s thought about worship. This article would like to share the contribution of Calvin’s thought that can serve as a guide and correction for contemporary worship. For this reason, I will discuss the principles of Calvin’s theology, which are applied in aspects of worship, Calvin's view of the so-called liturgical sins, and metaphors used by Calvin to explain worship. Methodologically, this article seeks to draw from and contextualize Calvin’s thoughts on worship but does not offer comprehensive and historical discussion in the strict sense. Calvin’s thoughts on worship not only go beyond the subject of the use of musical instruments and psalms but also has rich potential for the development of Christian worship for today.